TIME, to move forward? comment on “a universal outcome measure for headache treatments, care-delivery systems and economic analysis” - Raquel Gil-Gouveia (The Journal of Headache and Pain, 2022)
Abstract The paper from Steiner et al. suggests that an outcome measure expressed in time units may be an adequate method to assess the impact of headache disorders, regardless of diagnosis or health care setting, proving useful for cost-benefit analysis and health policy definition. Using time lost to each attack – weighted by disability – may prove to be a reliable measure to establish the effectiveness of acute treatment, but if considering also the attack frequency it could evaluate the effects of preventive strategies. A measure such as the Headache Gauge, which translates the proportion of time lost to headache -related disability, has proven to be applicable also in routine clinical practice as well, and can be tested in clinical trials and populational analysis. There are practical limitations, such as disability assessment and the need for prospective data collection to avoid recall bias but it seems consensual that impairment related to primary headache disorders is primarily driven by the TIME stolen from the perfect health status.